Interpretasi Citra untuk Analisis Kapasitas Sungai Unda sebagai Tampungan Lahar Dingin Erupsi Gunung Agung Bali - LESTARI, NI KADEK DIAN ASRI; TRIGUNASIH, NI MADE; DIBIA, I NYOMAN; SUYARTO, R. (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Imagery Interpretation for Analysis of Unda River Capacity to Retain Lahars Flow of Agung Volcano Eruption   This study aims to determine the flow capacity of Unda River to retain lahars flow of Agung Volcano eruption using a descriptive exploratory method, the data through field surveys and analysis of satellite imagery. Sampling was determined based on the gradient and river's meander to produce 14 samples and 13 segments in the river flow. The cross section of the river is measured at each sample point with the mean section method, then estimating the volume of the river by multiplying the area between the two sections with the distance of the sample point. The lahar flood hazard assessment uses the Laharz application with the lahars scenario 1 million m 3 ; 5 million m 3 ; and 10 million m 3 . The results of the study showed that the capacity volume of the Unda River was 26.336.548,79 m 3 . Estimated area affected by scenario 1 million m 3 covering 162,60 Ha; scenario 5 million m 3 covering 399,19 Ha; and the scenario of 10 million m 3 covering 533,77 Ha. The affected area reached 27 villages in the Karangasem Regency region and 20 villages in the Klungkung Regency area. The highest affected area for scenario of 1 million m 3 is Muncan Village about 32,70 Ha; scenario 5 million m 3 in Selat Village, Klungkung is 68,43 Ha; and the scenario of 10 million m 3 in Tangkas Village about 266,01 Ha. The type of land use that affected is rice field land about 458,08 Ha; moor / mixed garden at 71,33 Ha; settlements is 147,72 Ha; and shrubs about 3,98 Ha.